Evaluación de la sobrecarga en los cuidadores de los pacientes con enfermedad de Parkinson ambulatorios y sus factores de riesgo - Benavides,Olga (Sociedad Médica de Santiago, 2013)
Background: Parkinson disease (EPI) patients often require being assisted by others. These caregivers are exposed to a decrease in their quality of Ufe. Aim: To explore Parkinson disease patient features associated with a greater burden among their caregivers. Material ana Methods: Fifty one patients with Parkinson disease (aged 67 ± 12years, 29 men, with 8 ± 5years of disease) and their caregivers, were studied. Patients were assessed with the Unified Parkinson Disease Rating Scale III, the Hoehn & Yahr stage standardization, Parkinson s minimental test, the neurop-sychiatric inventory and the Beck Depression Inventory (IDB). The Zarit Burden Interview (ESZ) was applied to caregivers. Results: According to IDB, 45% of patients whose caregiverspresented little or no burden had a depression, compared to 78% of those whose caregivers had modérate or intense burden. (p < 0.01). The ESZ score of caregivers correlated significantly with Parkinson patients' age, IDB and axial involvement in the UPDRS-III (correlation coefficients ofOAp < 0.01, 0.6p < 0.01 and 0.46p < 0.01, respectively). Conclusions: Motor alterations, cognitive impairment and most importantly depression of patients with Parkinson disease are deteminants of burden for their caregivers.